Improvement of φ29 DNA polymerase amplification performance by fusion of DNA binding motifs - de Vega, Miguel (National Academy of Sciences, 2010)
Bacteriophage φ29 DNA polymerase is a unique enzyme endowed with two distinctive properties, high processivity and faithful polymerization coupled to strand displacement, that have led to the development of protocols to achieve isothermal amplification of limiting amounts of both circular plasmids and genomic DNA. To enhance the amplification efficiency of φ29 DNA polymerase, we have constructed chimerical DNA polymerases by fusing DNA binding domains to the C terminus of the polymerase. The results show that the addition of Helix-hairpin-Helix [(HhH)(2)] domains increases DNA binding of the hybrid polymerases without hindering their replication rate. In addition, the chimerical DNA polymerases display an improved and faithful multiply primed DNA amplification proficiency on both circular plasmids and genomic DNA and are unique φ29 DNA polymerase variants with enhanced amplification performance. The reported chimerical DNA polymerases will contribute to make φ29 DNA polymerase-based amplification technologies one of the most powerful tools for genomics.